Kontribusi Pendapatan Karyawan terhadap Ekonomi Keluarga (pada UMKM Coffee Shop di Kecamatan Telanai Pura Kota Jambi) - Enggo Estu; Selamet Rahmadi; Rosmeli Rosmeli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The purpose of this study was to determine the socio-economic characteristics of employees, employee income, and the contribution of employee income to family income in MSME coffee shops in Telanaipura District. The type of research is descriptive qualitative with the data collected being primary data and secondary data. Sample selection used purposive sampling with a total of 31 respondents. Data collection used questionnaires, observation and documentation. Data analysis used descriptive analysis and contribution formulas. The results showed that the socio-economic characteristics of employees in MSME coffee shops in Telanaipura District include the age of employees who are still in the young and productive age category, the majority of gender is female, high school educational background, length of service 1-2 years, the number of family members is 3-4 people with the number of dependents in the family 1-2 people. The income of employees in MSME coffee shops in Telanaipura District averages Rp. 3,234,535,- per month which is used for personal needs is Rp. 1,380,645,- per month and salary for family needs is Rp. 1,167,742,- per month. The contribution of employee income to family income in MSME coffee shops in Telanaipura District is 52.39%. This means that employee income in MSME coffee shops in Telanaipura District contributes significantly to family income, thus supporting the family economy.